The Role Of Waiters And Waitresses In Providing Restaurant Services At Grand Mercure Hotel Malang - Firly Yasir Rianto (Empat Sembilan Publisher, 2024)
This study aims to analyze the role of waiters and waitresses in providing food and beverage services at the Grand Mercure Hotel Malang. In the hospitality industry, good service quality is the main key to guest satisfaction, and waiters and waitresses play an important role in this. This study uses a qualitative descriptive method with data collected through direct observation and interviews with hotel staff. The results of the study show that waiters and waitresses at the Grand Mercure Hotel Malang have responsibilities that include table arrangements, food and beverage service, and order management. They are also involved in room service and banquet activities that require coordination and special skills. The service process includes several important stages, such as table setting, taking orders, as well as service and cleaning after the event. In addition, handling complaints and problems that arise during the service is also an important part of their duties. Obstacles that are often faced include communication problems, service delays, and equipment damage. The proposed solutions include increased training, improved operational procedures, and improved communication between staff. The study concludes that the role of waiters and waitresses is crucial in improving the quality of service in hotels, and there is a need for more effective training strategies and better management systems to overcome existing constraints.